Pendampingan Transformasi Metode Pengajaran Bahasa Arab dari Gramatikal ke Komunikatif Berbasis Kurikulum OBE (Outcome-Based Education) di Madrasah Darul Ulum Lombok Tengah - Ahmad Helwani Syafi’i; Syahrol Izhomi; Adwia; Zoeriah (BALE LITERASI, 2026)
This study aims to analyze and describe the process and impact of mentoring in transforming Arabic language teaching methods from a grammatical approach to a communicative approach based on Outcome-Based Education (OBE) at Darul Ulum Islamic School, Central Lombok. The study employed a Participatory Action Research (PAR) approach, actively involving teachers as key agents of change throughout the process. The research stages included needs assessment, program design, training workshops, classroom implementation, and continuous evaluation. The findings indicate that prior to the intervention, Arabic language instruction was predominantly grammar-oriented, focusing on structural rules, which resulted in low communicative competence among students. Following the mentoring program, there was a significant improvement in student engagement, speaking skills, and overall communicative performance. Additionally, teachers demonstrated a paradigm shift toward student-centered learning and were able to design measurable learning outcomes and performance-based assessments aligned with OBE principles. This study contributes to the development of an integrated Arabic language teaching model that combines Communicative Language Teaching (CLT) and Outcome-Based Education (OBE) within the context of Islamic schools. The findings suggest that practice-based mentoring is an effective strategy to enhance both teaching quality and teacher professionalism.